An Analysis Of Diction In Maya Angelou’s Selected Poems - Ayuni, Nurfitri; Maghdalena, Maghdalena; Basa, Rowela (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aimed to find out what are the types of diction used by Maya Angelou in selected poems, they are “Still I rise”, “Touched by an angel” and “Equality” based on the theory of Abrams (1999) for analyzing the types of diction. There are four types of diction according to Abrams: concrete, abstract, denotation, and connotation. Methodology: This study uses a descriptive qualitative method with content analysis based on Abrams' theory (1999) to analyze diction in three poems by Maya Angelou: